Influence variables for honey production using bees Apis mellifera in the Misantla region - Martell Tamanis, Annet Yeli; Lobato Rosales, Fasbiola Guadalupe; Landa Zárate, Margarito; Luna Chontal, Giovanni; García Santamaría, Luis Enrique; Fernandez Lambert, Gregorio (Revista Mexicana de Ciencias Agrícolas, 2019)
Various notes of electronic portals, documentaries and to a lesser extent scientific articles have reported interest in improving the production yield of honey by beehive. Among these works, climatic, social and technological factors can be reported in their dimensional form, where experts and specialists recognize that they contribute to improving honey production. Supported by apicultural experts, the Delphi method and the MICMAC structural analysis, this article reports the influence and dependence of 22 variables and their direct and indirect relationship with honey production in the intermunicipal region of Misantla of the apicultural district no. 52. Variables based on MICMAC are classified as key, regulatory, lever and autonomous. On a strategic level, the ‘location of the apiary’ related to the ‘diversity of honey flowering’ and the ‘time between the placement of the apiary and the honey harvest’, represent the key variables with the highest strategic value of 75/79, 61/79 and 63/79, respectively. Although the ‘flowering of honey species’ is a key variable for honey production, the result also indicates that this variable is not a determinant for the beekeeper to decide the ‘location of apiaries’. These results provide knowledge in four categories of influential variables in honey production so that the beekeeper reflects on his beekeeping practices and can design strategies and make decisions, to improve honey production yield.
Keywords: apiary; beehive; beekeeping production; honey; MICMAC